Strategi Dalam Penataan Pedagang Kaki Lima Di Kawasan Pantai Padang - Zakia ALdeo; Afifah Rahma Aulia; Yusuf Efendi; Syamsir Syamsir (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The purpose of the issuance of Regional Regulation No. 3 of 2014 is so that street vendors can meet the requirements and be monitored so they can move to a place provided by the Padang City Government. This decision was taken to create 6 cities of Padang that are comfortable, safe and beautiful. According to a survey conducted by researchers, the location of street vendors (PKL) has a very negative effect on the smoothness, cleanliness and orderliness of public spaces, which of course needs government support or government mapping to create comfort and convenience. Running road use works fine. With these considerations, the authors are interested in further analyzing regional regulations related to the arrangement and empowerment of street vendors in order to understand the real facts. Therefore, the author presents a mini study entitled "Strategy in structuring street vendors in the Padang Beach area".